تحليل أداء نظام ملاحة تكاملي INS/GPS/Mag./Baro. - شعيب إبراهيم; ريشة حسان; درة ياسين محمد (Latakia University Journal -Engineering Sciences Series, 2016)
تم في هذه المقالة استعراض بنية نظام ملاحة تكاملي مكون من وحدة حساسات عطالية المصنعة بتقنية MEMS ومستقبل GPS ووحدة بوصلات مغناطيسية مصنعة بتقنية MEMS وحساس ارتفاع بارومتري. كما تم بناء النظام التكاملي باستخدام مرشح كالمان الموسع Extended Kalman Filter (EKF). وذلك بنظام الحلقة المغلقة ذات التكامل البسيط Loosely Coupling Integration . بإجراء عدة تجارب جوية لتحصيل المعطيات الملاحية الحقيقية. استخدمت المعطيات الملاحية المحصلة في تحليل أداء نظام الملاحة التكاملي مع كل من مرشح كالمان EKF في البيئة البرمجية Matlab. تبين من خلال التحليل أن نظام الملاحة التكاملي أمّن خطأ أفقياً لا يتعدى 50 m. وبأجراء حجب متعمد لمعطيات GPS لفترات مختلفة من أجل اختبار أداء نظام الملاحة التكاملي في حال قطع إشارة GPS وتبين أن نظام الملاحة التكاملي يحقق دقة جيدة، حيث لم تتعد قيمة الخطأ الأفقي 200 m عند حجب معطيات GPS لفترة 120 ثانية. والتي يمكن عدها قيماً صغيرة ومقبولة مقارنة مع قيمة الخطأ الأفقي لوحدة الملاحة العطالية التي تصل إلى 8200 m عندما تعمل بشكل مستقل. This article reviews the structure of an integrated navigation system made up of unit inertial sensors manufactured by MEMS technology, a GPS Receiver unit, magnetic compasses manufactured by MEMS technology, and a high barometric sensor. The integrated system is built using an Extended Kalman Filter (EKF). This reviewing is performed with the use of a closed-loop system that has simple integration namely the Loosely Coupling Integration. After conducting several air tests to collect real navigational data, antipersonnel navigational data has been used to do the integrated navigation system analysis with EKF environment in the software Matlab. It has been noticed after the analysis that the complementary horizontal navigation system error does not exceed 50 m. With deliberate withholding of GPS data for different periods in order to test the performance of the integrated navigation system in case of withholding the GPS signal, we have found that the integrated navigation system achieves good accuracy, where the horizontal error does not exceed 200 m value when the withholding GPS data for 120 seconds. This can be considered as small and acceptable values compared with the horizontal error value for inertial navigation unit stim300 when operating independently of up to 8200 m